Chest Low-Dose Computed Tomography for Early Lung Cancer Diagnosis as an Opportunity to Diagnose Vertebral Fractures in HIV-Infected Smokers, an ANRS EP48 HIV CHEST Substudy. (1st July 2015) - Thouvenin, Yann; Makinson, Alain; Cournil, Amandine; Eymard-Duvernay, Sabrina; Lentz, Pierre; Delemazure, Anne-Sophie; Corneloup, Olivier; Fabre, Sylvie; Quesnoy, Mylène; Poire, Sylvain; Brillet, Pierre-Yves; Cyteval, Catherine; et al.
Abstract : Background: To estimate the prevalence of vertebral fractures on chest low-dose computed tomography (LDCT) in HIV-infected smokers. Methods: Cross-sectional study of vertebral fractures visualized on chest LDCT from a multicenter prospective cohort evaluating feasibility of chest LDCT for early lung cancer diagnosis in HIV-infected subjects. Subjects were included if 40 years or older, had been active smokers within the last 3 years of at least 20 pack-years, and had a CD4 T-lymphocyte nadir cell count <350 per microliter and an actual CD4 T-cell count >100 cells per microliter. Spinal reconstructed sagittal planes obtained from chest axial native acquisitions were blindly read by a musculoskeletal imaging specialist. Assessment of the fractured vertebra used Genant semiquantitative method. The study end point was the prevalence of at least 1 vertebral fracture. Results: Three hundred ninety-seven subjects were included. Median age was 49.5 years, median smoking history was 30 pack-years, median last CD4 count was 584 cells per microliter, and median CD4 nadir count was 168 cells per microliter; 90% of subjects had a viral load below 50 copies per milliliter. At least 1 fracture was visible in 46 (11.6%) subjects. In multivariate analysis, smoking ≥40 packs-years [OR = 2.5; 95% CI: (1.2 to 5.0)] was associated with an increased risk of vertebral fracture, while HIV viral load <200 copies per milliliter [OR = 0.3; 95% CI: (0.1 to 0.9)] was protective. Conclusions: Prevalence of vertebral fractures on chest LDCT was 11.6% in this high-risk population. Smoking cessation and early introduction of antiretroviral therapy for prevention of vertebral fractures could be beneficial. Chest LDCT is an opportunity to diagnose vertebral fractures.